Expanding the molecular spectrum of gene fusions in endometrial stromal sarcoma: Novel subunits of the chromatin remodeling complexes PRC2 and NuA4/TIP60 as alternative fusion partners. Issue 3 (7th December 2022) - Dermawan, Josephine K.; Dashti, Nooshin; Chiang, Sarah; Turashvili, Gulisa; Dickson, Brendan C.; Ellenson, Lora H.; Kirchner, Martina; Stenzinger, Albrecht; Mechtersheimer, Gunhild; Agaimy, Abbas; Antonescu, Cristina R.
Abstract: Endometrial stromal sarcomas (ESS) are morphologically and molecularly heterogeneous. We report novel gene fusions ( EPC1::EED, EPC1::EZH2, ING3::PHF1 ) identified by targeted RNA sequencing in five cases. The ING3::PHF1‐ fusion positive ESS presented in a 58‐year‐old female as extrauterine mesocolonic, ovarian masses, and displayed large, monomorphic ovoid‐to‐epithelioid cells arranged in solid sheets. The patient remained alive with disease 13 months after surgery. The three ESS with EPC1::EED occurred in the uterine corpus in patients with a median age of 58 years (range 27–62 years). One tumor showed a uniform epithelioid nested morphology, while the other two were composed of monomorphic spindle cells in fascicles with elevated mitotic figures, focal tumor cell necrosis, and lymphovascular invasion. At a median follow‐up of 20 months, two patients developed local recurrence, including one with concomitant distant metastasis, while one patient remained free of disease. All three patients were alive at the last follow‐up. The EPC1::EZH2‐ fusion positive ESS presented in a 52‐year‐old female in the uterus, and displayed uniform spindled cells arranged in short fascicles, with focally elevated mitotic activity but without necrosis. The patient remained free of disease 3 months after surgery. All cases were diffusely positive for CD10; four diffusely express estrogen and progesterone receptors. Our study expands the molecular spectrum of EPC1 and PHF1 ‐related gene fusions in ESS to include additional novel subunits of the PRC2 and/or NuA4/TIP60 complexes. These cases displayed a monomorphic epithelioid or spindled phenotype, spanning low‐grade and high‐grade cytomorphology, all expressing CD10 and commonly ER and PR, and are prone to local and/or distant spread.